Progress(es), Theories and Practices - Ming Kong, Mário S., author.
1 online resource
Keywords: "The texts presented in Proportion Harmonies and Identities (PHI) - Progress(es) - Theories and Practices were compiled with the intent to establish a platform for the presentation, interaction and dissemination of research. It aims also to foster the awareness of and discussion on the topics of Harmony and Proportion with a focus on different progress visions and readings relevant to Architecture, Arts and Humanities, Design, Engineering, Social and Natural Sciences, Technology and their importance and benefits for the community at large. Considering that the idea of progress is a major matrix for development, its theoretical and practical foundations have become the working tools of scientists, philosophers, and artists, who seek strategies and policies to accelerate the development process in different contexts."--Provided by publisher.